Proses Komunikasi Tim Program Kelurahan Bersinar Dalam Pencegahan Narkoba Di Kelurahan Tanah Seribu Binjai - Ratni Hardiana; Mazdalifah; Sakhyan Asmara (MUKASI: Jurnal Ilmu Komunikasi, 2022)
Kelurahan Bersinar (Narcotics-Free Village) program, initiated by the National Narcotics Agency of the Republic of Indonesia, involves various agencies. The objective of the research is to analyze the communication process in the program. The research employs interpretive paradigm with qualitative approach. The data are gathered by conducing in-depth interview, observation, documentation study, and library research. The gathered data are analyzed by using interactive method of Miles and Huberman. The research is done at the Kelurahan Tanah Seribu, Binjai, North Sumatera which is the first narcotics-free village in Binjai. The result of the research shows that the process of communication done by the team is through face to face communication, and through outdoor and indoor communication. The communication barriers found are late distribution of activity tehnical manual books, repeated materials, and people’s negative stigma to government employees taking care of the problems related to narcotics abuse.